2022
DOI: 10.1097/md.0000000000029669
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial ultrasound-guided transbronchial needle aspiration as a diagnostic modality for schwannoma: A case report

Abstract: Introduction: Schwannomas are the most common nerve sheath tumors in the paravertebral mediastinum. Although radiological imaging is helpful in diagnosing schwannomas, a definitive diagnosis is dependent on pathological features of a surgical specimen. For patients who require preoperative diagnosis, an incisional biopsy using minimally invasive surgery is preferred. Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is less commonly used for suspected schwannomas. Patient concerns:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Mediastinal cysts are congenital, benign conditions that account for approximately 12–30% of all mediastinal lesions ( 6 ). If the volume of a cyst expands, it can exert pressure on adjacent organs, thereby affecting the cardiac and pulmonary function of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Mediastinal cysts are congenital, benign conditions that account for approximately 12–30% of all mediastinal lesions ( 6 ). If the volume of a cyst expands, it can exert pressure on adjacent organs, thereby affecting the cardiac and pulmonary function of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Here we present a case of schwannoma diagnosed with EBUS‐IFB using SBFs. Diagnosis of neurogenic tumors requires histopathological and imaging examinations, which can be challenging, with the exception of cases where surgical biopsy is conducted 4,5 . Although several case reports have previously reported the diagnosis of schwannoma using EBUS‐TBNA alone, 11–15 a retrospective study of 86 neurogenic tumors of the mediastinum reported that the diagnosis was made in 84 cases using surgical specimens; two and three cases in which EBUS‐TBNA and TTB, respectively, were performed did not yield an accurate diagnosis of schwannoma 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of neurogenic tumors requires histopathological and imaging examinations, which can be challenging, with the exception of cases where surgical biopsy is conducted. 4 , 5 Although several case reports have previously reported the diagnosis of schwannoma using EBUS‐TBNA alone, 11 , 12 , 13 , 14 , 15 a retrospective study of 86 neurogenic tumors of the mediastinum reported that the diagnosis was made in 84 cases using surgical specimens; two and three cases in which EBUS‐TBNA and TTB, respectively, were performed did not yield an accurate diagnosis of schwannoma. 3 Herein, EBUS‐TBNA with four punctures yielded insufficient specimens for diagnosis, and the addition of EBUS‐IFB using SBFs was diagnostically efficacious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 b); (3) for hemangioma , both of them paid much attention to the obvious internal honeycomb structure and the enhanced echo behind the lesion (Fig. 4 c); (4) for neurinoma [ 31 , 32 ], both of them focused on the “bright cap sign” of the lesions (Fig. 4 d); (5) for epidermal cyst [ 33 , 34 ], both of them were very concerned about the enhancement of the echo behind the lesion (Fig.…”
Section: Discussionmentioning
confidence: 99%